(untitled) (Research, Society and Development, 2020)
Religious teachings that are part of humanity’s heritage are constantly being reinterpreted as reality and social values change. In this process, literature also makes its contribution, questioning some values and revealing its character of imposition and social domination. In this work, we will analyze how this happens in two novels by American writers, Alice Walker’s The Purple Color and Bernard Malamud’s The Fixer. Coming from different ethnic groups, these writers question the traditional representation of God from the reality of their social group, Walker from the perspective of a black feminist and activist while Malamud does it from the perspective of Judaism. Their questioning will be determined by the injustices their groups suffer as social minorities. In the end, we will see that, despite coming from different social backgrounds, at the root of the questioning of the two writers is the ideal of fighting for freedom itself, which is such a strong value in American culture and society. Thus, this becomes the parameter and measure for questioning secular religious notions in the novels of these authors.